Ovarian tumor cases that were preoperatively diagnosed as benign but postoperatively confirmed as borderline or malignant after laparoscopic surgery - Yasushi Kotani; Masahiko Umemoto; Takako Tobiume; Mitsuru Shiota (Wolters Kluwer Medknow Publications, 2013)
Objective: Laparoscopic surgery is the gold standard for benign ovarian tumors because of its overall improved quality of life (QOL). However, some tumors diagnosed preoperatively as benign may be proven to be malignant by postoperative studies. The standard approach for the removal of a malignant ovarian tumor in our hospital is via laparotomy; however, there is no referential prognostic data on malignancies that are excised laparoscopically. To evaluate clinical and histological factors and prognosis, this study retrospectively reviewed patients who underwent surgery in our hospital, based on a preoperative diagnosis of benignancy, but later postoperative testing proved their tumors to be borderline or malignant. Participants and methods: The study group comprised 1322 women who underwent a laparoscopic procedure in our hospital on the basis of a preoperative diagnosis of a benign ovarian tumor. The procedures were performed between 1995 and 2011. The rate of borderline and malignant cases, histology, and postoperative treatment were investigated. Results: Of the 1322 patients, 15 (1.1%) patients were postoperatively diagnosed as having a borderline malignancy with various histological types and all of these patients had a good prognosis; four (0.3%) patients were postoperatively diagnosed as having a malignant tumor with various histological types; of these patients, two patients required emergency surgery. All four patients underwent additional surgery and chemotherapy with no recurrence to date. Conclusion: Some tumors diagnosed preoperatively as benign proved postoperatively to be malignant. Appropriate postoperative treatment effectively improved the prognosis. Particular attention should be paid to a possible occult malignancy that may manifest postoperatively, especially in patients who underwent emergency surgery. We recommend preoperative magnetic resonance imaging, even for emergency cases, to improve preoperative diagnosis.